A new catostomid fish (Ostariophysi, Cypriniformes) from the Eocene Kishenehn Formation and remarks on the North American species of †Amyzon Cope, 1872. (13th June 2016) - Liu, Juan; Wilson, Mark V.H.; Murray, Alison M.
Abstract: Fossil catostomids were very rare prior to the Eocene. After the Eocene, they suddenly decreased in diversity in Asia while becoming common fishes in the North American fauna. Knowledge of the taxonomy, diversity, and distribution of Eocene catostomids is critical to understanding the evolution of this fish group. We herein describe a new catostomid species of the genus † Amyzon Cope, 1872 from the Eocene Kishenehn Formation in Montana, USA. The new species, † Amyzon kishenehnicum, differs from known species of † Amyzon in having hypurals 2 and 3 consistently fused to the compound centrum proximally, and differs from other Eocene catostomids in that the pelvic bone is intermediately forked. All our phylogenetic analyses suggest that the new species is the sister group of † A . aggregatum Wilson, 1977 and that † Amyzon is the most basal clade of the Catostomidae. We reassessed the osteological characters of the North American species of † Amyzon from a large number of well-preserved specimens of the new species, as well as † A . gosiutense Grande et al., 1982 and † A . aggregatum . Osteological characters newly discovered indicate that † A . gosiutense is not a junior synonym of † A . aggregatum, but should be retained as a distinct species.